O papel dos custos de transação na gestão da cadeia de suprimentos verde - Silva, Flavia Cristina da (2021)
The close link between economic growth and environmental destruction is risking the sustainability of the current economic development model. Faced with the scarcity of natural resources, companies are forced to improve their processes to ensure the sustainability of their operations, with a view to increasing both operational and environmental performances. This study aims to investigate the influence of transaction costs on the relationship between green supply chain management and the use of environmental technologies for the performance of the supply chain. Therefore, the exploratory and descriptive study was developed in three consecutive phases: literature review, exploratory research, and descriptive research. The focus of this work is on the operations of the intermediate goods and durable and non-durable consumer goods industries. The first phase identifies 157 assertions that were submitted to the assessment of managers concerned with operations in the subsequent phase. The interviews allowed for the comparison of concepts between practices adopted and the refinement of the research instrument, which now has 48 assertions for applications in the field. In the last stage of the study, the questionnaire was submitted to 257 respondents from industries in different sectors and distributed throughout the country. The structural equation modeling this two-stage approach permits the identification of transaction costs which negatively influence the relationship between green supply chain management and chain performance, while environmental technologies exert a positive mediation factor in this relationship. The contributions of this study to academic practices consist in providing subsidies for a better understanding of the relationships between the constructs through a new theoretical perspective, in which the circular economy is seen as a dimension of the chain's performance. Regarding contributions to managerial practices, the results contribute to a better understanding of the relationships established between members of the supply chain and its effects on GCSV practices and the use of environmental technologies, as well as highlighting the positive relationship of a sustainable posture in corporate enterprise to increase the performance of the chain. Such elements can support strategic decisions to increase competitiveness. Regarding contributions to public policies, this study found the need to implement programs to disseminate knowledge about the scope of environmental technologies in production processes, as well as incentives to incorporate such technologies into productive activities.